2020
DOI: 10.3390/jcm9020582
|View full text |Cite
|
Sign up to set email alerts
|

A Population-Based Study of Diabetes during Pregnancy in Spain (2009–2015): Trends in Incidence, Obstetric Interventions, and Pregnancy Outcomes

Abstract: (1) Background: We examined trends in incidence and outcomes in women with existing type 1 diabetes mellitus (T1DM), type 2 diabetes mellitus (T2DM) and gestational diabetes mellitus (GDM) compared with a control group without diabetes. (2) Methods: This was an observational, retrospective epidemiological study using the National Hospital Discharge Database. (3) Results: There were 2,481,479 deliveries in Spain between 2009 and 2015 (5561 mothers with T1DM, 4391 with T2DM, and 130,980 with GDM). Incidence and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 37 publications
(79 reference statements)
0
21
0
Order By: Relevance
“…Sixteen studies were retrospective, two were prospective, one was cross-sectional and one was unspecified. Nine studies reported adverse outcomes for pregestational diabetes, combining data for T1DM and T2DM [ 16 , 20 , 22 , 25 , 27 , 43 , 44 , 45 , 46 ], while 11 studies reported data for T1DM and T2DM, separately [ 14 , 15 , 17 , 21 , 24 , 47 , 48 , 49 , 50 , 51 , 52 ]. These studies reported on various maternal and neonatal short-term pregnancy adverse outcomes, of which 13 are summarised in this review.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sixteen studies were retrospective, two were prospective, one was cross-sectional and one was unspecified. Nine studies reported adverse outcomes for pregestational diabetes, combining data for T1DM and T2DM [ 16 , 20 , 22 , 25 , 27 , 43 , 44 , 45 , 46 ], while 11 studies reported data for T1DM and T2DM, separately [ 14 , 15 , 17 , 21 , 24 , 47 , 48 , 49 , 50 , 51 , 52 ]. These studies reported on various maternal and neonatal short-term pregnancy adverse outcomes, of which 13 are summarised in this review.…”
Section: Resultsmentioning
confidence: 99%
“…However, two studies reported no difference in the rates of stillbirths between pregestational diabetes and GDM [ 20 , 45 ]. When comparing T1DM and T2DM separately with GDM, higher rates of stillbirths were reported in pregestational T1DM and T2DM compared to GDM in three studies [ 17 , 24 , 49 ], while Huddle et al, 1993, reported higher rates in T2DM (4.7%) compared to T1DM (3.3%) and GDM (4.0%) with the latter occurring at a similar rate [ 47 ]. Altogether, these results demonstrate that stillbirths are more common in neonates born to mothers with pregestational T1DM and T2DM compared to neonates born to mothers with GDM.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have separated between the neonatal outcomes of women with different types of preexisting diabetes. In a population-based study of diabetes during pregnancy in Spain (2009–2015), pregestational type 1 diabetes was associated with more severe neonatal morbidity, preterm birth (RR 3.32; 95% CI 3.14–3.51), and fetal overgrowth (RR 8.05; 95% CI 7.41–8.75) [ 24 ].…”
Section: Congenital Malformations and Diabetes In Pregnancymentioning
confidence: 99%
“…Only 2% of the patients in our study had T2DM. However, as there is a concerning trend worldwide ofanincreaseinthe maternal age and prevalence of maternal obesity, there is a justified concern that the prevalence of T2DM in pregnancy may increase in future decades [ 38 ]. The lower prevalence of T2DM among women with diabetes in our study may be due to the lower fertility rates of women with pre-gestational T2DM and its association with obesity and polycystic ovarian syndrome, both contributing to the fertility decrease [ 6 ].…”
Section: Discussionmentioning
confidence: 99%